New record of the genus Stereodytis Meyrick, 1914 (Lepidoptera: Oecophoridae) from Japan with the description of a new species - Tomura, Shunsuke; Yagi, Sadahisa; Hirowatari, Toshiya (Zootaxa, 2023)
A new species Stereodytis eclipsia Tomura & Hirowatari sp. nov. from Japan is described. Images of the imagos, male and female genitalia, larval biology, feeding habits, and molecular data are provided. Additionally, its systematic position and the possibility that this species was invasive in recent years are discussed.